(untitled) (PANGEEA, 2025)
ABSTRACT: In this paper we analyze the main river bed changes in Trascău Mountains, situated on the west edge of the Transylvanian Depression. Were studied the recorded data from 11 hydrometric stations, arranged in four river basins: Aiud, Geoagiu, Galda and Ampoi. The characteristics analyzed are: longitudinal section, transversal section and river flow. Analysis of the three features has led to these conclusions: upstream of the limestone the large white are predominant, în the limestone crossing area are predominant the white limited in width and in the aisle of Mures, is clearly defined shape (rectangle, trapezoid).